Investment in sustainability university green campus projects: the case of Universiti Malaya, Malaysia - Rui, Wang; Lee, Ting Ni; Abdul-Samad, Zulkiflee; Mustaffa, Muhammad Hadi; Mahdzir, Mazura; Ya’cob@Ya’acob, Nafisah; Syed Khuzzan Alhabshi, Sh Mazlina (Malaysian Institute of Planners (MIP), 2025)
Sustainability has become a central priority in higher education, with universities worldwide investing in initiatives to reduce environmental impact and promote long-term responsibility. Despite this trend, there remains limited comparative research on Universiti Malaya’s (UM) sustainability practices concerning established green campuses. This study addresses this gap by examining UM’s sustainability investments and identifying areas for improvement. A quantitative approach was adopted, involving a questionnaire survey of 361 UM employees. Data were analysed using the Relative Importance Index (RII) to rank the significance of sustainability initiatives. The findings reveal waste management and external stakeholder collaborations are the most prominent investment areas. At the same time, other initiatives are perceived at medium to high levels of importance, indicating a solid foundation for UM’s sustainability efforts. The study recommends strengthening institutional strategies by benchmarking UM’s practices against international green campus models. The results contribute to advancing UM’s environmental responsibility and aligning its efforts with broader sustainability goals.